Annual and seasonal patterns in etiologies of pediatric community-acquired pneumonia due to respiratory viruses and Mycoplasma pneumoniae requiring hospitalization in South Korea - Lee, Eun; Kim, Chul-Hong; Lee, Yong Ju; Kim, Hyo-Bin; Kim, Bong-Seong; Kim, Hyung Young; Kim, Yunsun; Kim, Sangyoung; Park, Chorong; Seo, Ju-Hee; Sol, In Suk; Sung, Myongsoon; et al. (BMC infectious diseases, 2020)
Background Community–acquired pneumonia (CAP) is one of the leading worldwide causes of childhood morbidity and mortality. Its disease burden varies by age and etiology and is time dependent. We aimed to investigate the annual and seasonal patterns in etiologies of pediatric CAP requiring hospitalization. Methods We conducted a retrospective study in 30,994 children (aged 0–18 years) with CAP between 2010 and 2015 at 23 nationwide hospitals in South Korea. Mycoplasma pneumoniae (MP) pneumonia was clinically classified as macrolide-sensitive MP, macrolide-less effective MP (MLEP), and macrolide-refractory MP (MRMP) based on fever duration after initiation of macrolide treatment, regardless of the results of in vitro macrolide sensitivity tests. Results MP and respiratory syncytial virus (RSV) were the two most commonly identified pathogens of CAP. With the two epidemics of MP pneumonia (2011 and 2015), the rates of clinical MLEP and MRMP pneumonia showed increasing trends of 36.4% of the total MP pneumonia. In children < 2 years of age, RSV (34.0%) was the most common cause of CAP, followed by MP (9.4%); however, MP was the most common cause of CAP in children aged 2–18 years of age (45.3%). Systemic corticosteroid was most commonly administered for MP pneumonia. The rate of hospitalization in intensive care units was the highest for RSV pneumonia, and ventilator care was most commonly needed in cases of adenovirus pneumonia. Conclusions The present study provides fundamental data to establish public health policies to decrease the disease burden due to CAP and improve pediatric health.